Merrifieldia tridactyla - Ustjuzhanin, P. Ya.; Kovtunovich, V. N. (Zenodo, 2018)
Merrifieldia tridactyla (Linnaeus, 1758) NOTES. This species was recorded from Azerbaijan by Arenberger (2013). DISTRIBUTION. Europe, the Caucasus, Turkey, Iran, Kazakhstan, Southern Ural, south of western Siberia, western Yakutia. Published as part of Ustjuzhanin, P. Ya. & Kovtunovich, V. N., 2018, Fauna of plume moths (Lepidoptera: Pterophoridae) of Azerbaijan, pp. 16-24 in Far Eastern Entomologist 352 on page 23, DOI:10.25221/fee.352.4, http://zenodo.org/record/7164067